Strategy for Implementing the Hidden Curriculum for the Arabic Language Teacher at the Secondary Stage in TMI Al-Amien for Female - Wahyuni, Sri; Hanun, Bisyarotul (Universitas Al-Amien Prenduan, 2024)
This article aims to analyze the strategy for implementing the hidden curriculum for Arabic teachers as well as the supporting and inhibiting factors at TMI Al-Amien Prenduan. This research uses a qualitative approach with a descriptive type. Data sources were obtained from Arabic language teachers, master teachers and academics. The data collection methods used are observation, interviews and documentation. Data analysis is carried out by reducing data, presenting data and drawing conclusions. Meanwhile, the technique used to check the validity of the data is source triangulation. The results of this research are the hidden curriculum strategy used by Arabic language teachers at Marhalah Tsanawiyah in the form of applying I'dad tadris and serving as an example in the application of Arabic. The supporting factor in implementing the hidden curriculum is the role of the master teacher in planning the hidden curriculum for the Arabic language teacher himself. Meanwhile, the inhibiting factors are the lack of understanding of Arabic language teachers regarding the hidden curriculum theory and the small number of Arabic language teachers who study in the field of Tarbiyah.